FONTAN CIRCULATION AND PREGNANCY: IS IT POSSIBLE - Dorothea Kusumaningrat; Ellenora R Mustikaningrat; Gerardo AK Laksono; Paul L Tahalele (JOURNAL OF WIDYA MEDIKA JUNIOR, 2023)
More than 85% of congenital heart disease in children survive to adulthood according to recent advances in pediatric cardiology and heart surgery practice. Fifty percent of  this population is made up of women, most of whom have reached child bearing age. In this group of patients, pregnancy represents a new challenge, whose natural history has been modified by surgery. In Fontan circulation,  the ventricle unable to compensate for the major restriction in the bottleneck and non physiological suction have to pull blood through the lungs, although the ventricles provide the driving force for the circuit.  Women with an adequate Fontan circulation can become pregnant without clinically significant long term sequele.  Pre-marital and pre-pregnancy consultation is important. A close collaboration between cardiologist, obstetrician and anaesthesiologist is mandatory in order to get the best outcome of pregnancy.